Two-dimensional impurity imaging in deep Antarctic ice cores: snapshots of three climatic periods and implications for high-resolution signal interpretation - Bohleber, Pascal; Roman, Marco; Šala, Martin; Delmonte, Barbara; Stenni, Barbara; Barbante, Carlo (The Cryosphere, 2021)
Due to its micrometer-scale resolution and inherently micro-destructive nature, laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) is particularly suited to exploring the thin and closely spaced layers in the oldest sections of polar ice cores. Recent adaptions to the LA-ICP-MS instrumentation mean we have faster washout times allowing state-of-the-art 2-D imaging of an ice core. This new method has great potential especially when applied to the localization of impurities on the ice sample, something that is crucial, to avoiding misinterpretation of the ultra-fine-resolution signals. Here we present the first results of the application of LA-ICP-MS elemental imaging to the analysis of selected glacial and interglacial samples from the Talos Dome and EPICA Dome C ice cores from central Antarctica. The localization of impurities from both marine and terrestrial sources is discussed, with special emphasis on observing a connection with the network of grain boundaries and differences between different climatic periods. Scale-dependent i mage analysis shows that the spatial significance of a single line profile along the main core axis increases systematically as the imprint of the grain boundaries weakens. It is demon-strated how instrumental settings can be adapted to suit the purpose of the analysis, i.e., by either employing LA-ICP-MS to study the interplay between impurities and the ice microstructure or to investigate the extremely thin climate proxy signals in deep polar ice.